Pengembangan Media Buku Saku Elektronik Berbasis Mind Mapping Materi Bangun Ruang Kelas V Sd Gugus Sultan Fatah Kecamatan Bonang Kabupaten Demak - Laili Istiqomah; Su’ad Su’ad; Gunawan Setiadi (Peneliti.net, 2023)
The background of this research is the text book as one of studying media used by the students is unpractical, incomplete, unattractive, and does not use the development of the newest technology of communication information. The identiﬁcation of the problem of this research is how are the development, application, effectivity of mind maping based - electronic pocket book media on geometry material for ﬁfth grade students. The objective of this research are to produce the mind maping based - electronic pocket book media on geometry material, to describe the ap‐ plication, and to test the effectivity of the mind maping based - electronic pocket book media on geometry material, to increase the ﬁfth grade students' study result. The design of this research is research and development (R and D). The data collection techniques of this research are questionnaire, interview, test,and documentary. The result of this research based on the qualiﬁcation value of expert validation shows that this mind maping based - electronic pocket book media on geometry material is eligible to be used as a media in learning process. Further more, the use of mind maping based - electronic pocket book media on geometry material is effective to increase mathematic study result of ﬁfth grade students, with the average of 75% N-gain score of experimental group.The conclusion of this study is that the feasibility and effectivity of based-electronic pocket book media on geometry on mind mapping is proven feasible and effective can improve student learning outcomes of fifth grade students. The conclusion of this research is the eligibility of mind maping based - electronic pocket book media on geometry material is eligibly proven and able to increase the ﬁfth grade students' studying achievement. The suggestions are that it is expected that teachers are able to apply mind maping based - electronic pocket book media on the similar or other material and it needs to be improved.